Redenomination risk in eurozone corporate bond spreads. Issue 13 (2nd September 2021) - Bleaney, Michael; Veleanu, Veronica
Abstract : We investigate the risk spillover from euro area government bond spreads (relative to a safe German government bond of similar maturity) to nonfinancial corporate bonds in France, the Netherlands ('hard' euro-area countries), and Italy, Portugal and Spain ('soft' euro-area countries). In addition to standard firm- and bond-specific determinants of corporate bonds (capturing liquidity and tax effects, and other euro area macroeconomic risks), we show that there is significant risk transfer from government bonds to the nonfinancial corporate sector. After decomposing the government bond spread into a default risk and a currency redenomination risk component, associated with a possible split in the euro, we find that redenomination risk has been a significant factor in the pricing of corporate bonds, particularly in the 'soft' euro-area countries.